Mikrotik Network Workshop and Basic Training to Improve TKJ Student Competencies at SMK Bina Taruna 2 Medan - Chairul Imam; Dinur Syahputra; Amril (Outline Publisher, 2026)
The development of information technology requires vocational education to improve students' skills in computer networking and system administration. One highly sought-after skill in the industry today is the ability to set up and manage networks using Mikrotik RouterOS. Responding to this need, the Community Service Team (PKM) from the Indonesian Community Development University (UPI) and Battuta University collaborated to organize a workshop and basic Mikrotik training for Computer and Network Engineering (TKJ) students at SMK Bina Taruna 2 Medan through a guest teacher program. This activity was attended by 25 grade XII TKJ students with teaching methods that included material delivery, hands-on practice, and technical support. The material taught included the basics of computer networking, IP address settings, DHCP servers, hotspots, and routing with Mikrotik RouterOS. Assessment of the activity was carried out through pretests and posttests to assess the improvement in students' understanding and skills. The assessment results showed that the average student score increased from 56.4 in the pretest to 84.7 in the posttest, which is an increase of 50.1%. In addition, 88% of participants were able to perform basic Mikrotik configuration independently after participating in the training. This workshop not only improves students' technical skills, but also strengthens collaboration between universities and vocational high schools to support practical learning according to the needs of industry and the world of work.